2020
DOI: 10.1142/s0217984920500104
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive Flying Ad-hoc Network (FANET) for disaster response operations to improve quality of service (QoS)

Abstract: Flying Ad-hoc Networks (FANETs) and Unmanned Aerial Vehicles (UAVs) are widely utilized in various rescues, disaster management and military operations nowadays. The limited battery power and high mobility of UAVs create problems like small flight duration and unproductive routing. In this paper, these problems will be reduced by using efficient hybrid K-Means-Fruit Fly Optimization Clustering Algorithm (KFFOCA). The performance and efficiency of K-Means clustering is improved by utilizing the Fruit Fly Optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…In the study, the route identification function is used to select a route that considers both the remaining energy of the nodes and their Euclidean distance from one another. The Fruit Fly Optimization Algorithm (FFOA) improves the functionality and efficiency of clustering with K-Means and is compared to other optimization approaches, such as comprehensive learning particle swarm optimizer (CLPSO), classification of Compositional-Aware COrrelation NETworks (CACONET), Grey Wolf Optimization Based Clustering In Vehicular Ad-Hoc Networks (GWOCNET), and Energy-aware Cluster-based Routing in FANETs ECRNET [50]. These comparisons are made according to various performance characteristics that the FFOA exhibits.…”
Section: ) Bio-inspiredmentioning
confidence: 99%
“…In the study, the route identification function is used to select a route that considers both the remaining energy of the nodes and their Euclidean distance from one another. The Fruit Fly Optimization Algorithm (FFOA) improves the functionality and efficiency of clustering with K-Means and is compared to other optimization approaches, such as comprehensive learning particle swarm optimizer (CLPSO), classification of Compositional-Aware COrrelation NETworks (CACONET), Grey Wolf Optimization Based Clustering In Vehicular Ad-Hoc Networks (GWOCNET), and Energy-aware Cluster-based Routing in FANETs ECRNET [50]. These comparisons are made according to various performance characteristics that the FFOA exhibits.…”
Section: ) Bio-inspiredmentioning
confidence: 99%
“…[14] recommended Using a hybrid FANETs UAV clustering scheme, which considers the impact of mobility on the election of cluster heads, and improves the hybrid metaheuristic algorithm to improve clustering efficiency, thereby enhancing the lifespan of the system but UAV clustering scheme at the same time has high complexity. An adaptive flying Ad-hoc network [15] improves the performance and efficiency of K-Means clustering by means of fruit fly optimization algorithm, but it has high complexity and fails to assign weights for the degree of impact of the performance metrics, which affects the balance of the network structure.…”
Section: Introductionmentioning
confidence: 99%
“…In [6], authors have studied ground user communication through a UAV-assisted relay network to minimize the network's energy consumption. In [7], authors have investigated UAV-assisted communication for disaster management using a Fruit Fly optimization clustering algorithm. In [8], authors have shown that UAV provides ground node coverage in post-disaster scenarios and evaluates the optimal relay hops of the device-to-device (D2D) wireless network.…”
Section: Introductionmentioning
confidence: 99%